Answer:
T = (T_o + W/2α (1 + √(4αT_o/(W) + 1)] has been proved!
Step-by-step explanation:
We know that efficiency of pump is given by;
η = (Q/t)/P
Where;
P = the power consumed in the house
Q/t = the rejected power.
Now, P can also be expressed as W/t
Likewise, Q/t can also be expressed as; α(T - T_o)
From the question, pump consumed power of W. Thus, P = W in this case.
So, efficiency can be expressed as;
η = (α(T - T_o))/(W) - - - - (1)
Now, for the carnot engine of the pump, efficiency is expressed as;
η = T/(T - T_o) - - - - (2)
Equating equation 1 and 2,we have;
(α(T - T_o))/(W) = T/(T - T_o)
α(T - T_o)² = WT
Expanding, we have;
T² - (2T•T_o) + T_o² = WT/α
T² - (2T•T_o + WT/α) + T_o² = 0
T² -T(2T_o + W/α) + T_o² = 0
To find T, let's use quadratic formula which is;
x = [-b ± √(b² - 4ac)]/2a
T = -(-(2T_o + W/α)) ± √(-(2T_o + W/α)² - (4•1•T_o²)]/(2•1)
T = (2T_o + W/α)) ± √((-2T_o - W/α)² - (4T_o²)]/(2)
T = (2T_o + W/α)) ± √((4T_o² + 2T_o•W/α + (W/α)² - 4T_o²)]/(2)
T = (2T_o + W/α)) ± √(2T_o•W/α + (W/α)²)]/(2)
T = (T_o + W/2α)) ± (1/2)√(2T_o•W/α + (W/α)²)]
T = (T_o + W/2α)) ± (W/2α)√(4T_o/(W/α) + 1)]
T = (T_o + W/2α)) ± (W/2α)√(4αT_o/(W) + 1)]
Now, let's arrange to correspond with what's in the question. And it means we will make use of the positive sign where we have ±.
Thus;
T = (T_o + W/2α (1 + 1√(4αT_o/(W) + 1)]
T = (T_o + W/2α (1 + √(4αT_o/(W) + 1)]